What factors are key to generate a university entrepreneurial ecosystem? - Salviati, Carlos Francisco José (2021)
Nowadays, the entrepreneurial university approach is gaining strength, as one that develops a university entrepreneurial ecosystem that stimulates entrepreneurship in its students. In this sense, the research aims to delve into the concept of university entrepreneurial ecosystem and identify the main factors that generate it, based on an exploratory and qualitative study, reviewing recent literature in the Scopus, ScienceDirect and EBSCO databases. The results allow us to identify six key factors that generate a university entrepreneurial ecosystem, highlighting the strategic commitment and institutional entrepreneurial culture, resource allocation and entrepreneurship education. It is concluded that society demands that universities fulfil a third mission, which is to promote entrepreneurship, therefore it is necessary to continue to deepen the factors that influence the creation of a university entrepreneurial ecosystem.